Five-star Stranger : a novel - Tang, Kat (Scribner, 2024)
"Would you hire someone to be the best man at your wedding? Your stand-in brother? Your husband? In Kat Tang's exciting and resonant debut, a "Rental Stranger"--a companion hired under various guises--walks the line between personal and professional in surprising new ways. Five-Star Stranger follows a man who is a top-rated performer on the "Rental Stranger" app, where users can hire a pretend fiancé, Referred to only as Stranger, the narrator navigates New York City under the guise of the characters he plays, always maintaining a professional distance from his clients. In an age where online ratings are all-powerful, Five-Star Stranger follows the adventures of a top-rated man on the "Rental Stranger" app--a place where users can hire a a pretend fiancé, a wingman, or an extra mourner for a funeral. Referred to only as Stranger, the narrator navigates New York City under the guise of characters he plays, always maintaining a professional distance from his clients. When a nosy patron threatens to upend his long-term role as father to a young girl, Stranger begins to reckon with his attachment to his pretend daughter, her mother, and his own fraught past. Now, he must confront the boundaries he has drawn and explore the legacy of abandonment that shaped his life. Five-Star Stranger is a strikingly vivid novel about the commodification of relationships in a gig economy, isolation in a hyperconnected world, and the risk of asking for what we want from those who cannot give. This is the story of a man who finds out who he is by being anyone but himself"--